CIVIL JUSTICE IN CHINA - Y. Fu; X. Meng (BRICS Law Journal)
This article presents a basic and comprehensive introduction of Chinese civil justice. It gives a complete picture of Chinese civil justice, including the brief history, the court and judge system, the outline of the procedure, and the internationalization. Through the introduction, one can find that Chinese civil procedure law is a mixture of Soviet procedural concept, Chinese local culture, and western procedural concept and rules. It is still a developing procedure and experiences a process from resisting western procedural concept to gradually accepting and learning from it. It used to be a supra-inquisitorial trial model with overwhelming focus on conciliation, but is now transforming to aparty disposition trial model with preference to conciliation under the premise of voluntariness. With the globalization of economy, the international cooperation of China, especially with the BRICS countries, will also become more and more important.